2017
DOI: 10.1371/journal.ppat.1006799
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 controls innate immune and autophagy responses to TLR-mediated signalling by the intracellular bacteria Listeria monocytogenes

Abstract: Recent evidence on HDAC6 function underlines its role as a key protein in the innate immune response to viral infection. However, whether HDAC6 regulates innate immunity during bacterial infection remains unexplored. To assess the role of HDAC6 in the regulation of defence mechanisms against intracellular bacteria, we used the Listeria monocytogenes (Lm) infection model. Our data show that Hdac6-/- bone marrow-derived dendritic cells (BMDCs) have a higher bacterial load than Hdac6+/+ cells, correlating with we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 71 publications
(76 reference statements)
3
42
0
Order By: Relevance
“…The role of HDAC6 in the adaptive CD4 + T‐cell response has been studied in several autoimmune and inflammatory situations, such as colitis and cardiac allograft rejection . In the process of an innate immune response to fight against intracellular bacterial infections, HDAC6 participates in the indication of the pro‐inflammatory transcriptional program through the Toll‐like receptor pathway, which is triggered by sensing of cell‐surface and endo‐phagosomal bacteria …”
Section: Structure and Function Of Hdac6mentioning
confidence: 99%
See 2 more Smart Citations
“…The role of HDAC6 in the adaptive CD4 + T‐cell response has been studied in several autoimmune and inflammatory situations, such as colitis and cardiac allograft rejection . In the process of an innate immune response to fight against intracellular bacterial infections, HDAC6 participates in the indication of the pro‐inflammatory transcriptional program through the Toll‐like receptor pathway, which is triggered by sensing of cell‐surface and endo‐phagosomal bacteria …”
Section: Structure and Function Of Hdac6mentioning
confidence: 99%
“…Histone deacetylase 6 (HDAC6) is a unique member of the HDAC family that has been shown to be involved in multiple cellular processes, including cell migration and intracellular transport . Recent studies also showed the vital role of HDAC6 in the innate immune response to intracellular bacterial infections through Toll‐like receptor‐mediated signaling . Improper activation of HDAC6 has been observed in a variety of diseases, including cancer and neurodegenerative disorders, and small molecule drugs targeting HDAC6 are under active investigation as therapeutic agents .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC6 has been reported to modulate many signaling pathways that could modulate anti-viral immune responses including NF-κB, ERK, and inflammasome activation (27,40,41). We examined some key signaling components in anti-viral responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the innate arm of the immune system, HDAC6 has been found to control LPS-induced activation of macrophage and their subsequent production of pro-inflammatory cytokines 55 . In response to bacterial infection, HDAC6 facilitates bacterial autophagy by dendritic cells and maintains proper activation of TLR signaling in these cells 56 . Intriguingly, these researchers also found that the bone marrow derived dendritic cells (BMDCs) obtained from HDAC6 KO mice had reduced phosphorylation of MAPK signaling components in response to bacterial infection 56 .…”
Section: Implications Of Co-targeting Hdac6 and The Mapk Pathway In Imentioning
confidence: 99%